Ultrasonic method development of fluid flow velocity measurement - Білинський, Йосип Йосипович; Гладишевський, Микола Володимирович (Technology audit and production reserves, 2015)
In this article short analysis was done on main ultrasonic methods and means of fluid and gaseous flow control. New mathematical model of ultrasound wave distribution in fluid was proposed and ultrasonic method of fluid flow measurement on its basis. After research of various scientific works regarding near size of ultrasonic transducers a mathematical equation was derived that shows ultrasound frequency dependency on fluid flow velocity. Consequently, stated mathematical model was simulated in Matlab environment shoving some efficient results. Research on physics process of forming a sound wave in piezoelectric elements helped to discover frequency dependency on flow speed, which in turn made it possible, due to the new approach, to develop a mean of flow rate measurement and furthermore to propose perspective fluid and gas flow meters.